(untitled) (Management and Connections Journal, 2025)
Creativity management has been of growing interest in academia and among practitioners, who are seeking greater competitive advantage for their organizations. This interest has increased the number of scientific articles seeking to understand how the creative process takes place and what factors can influence creativity. The aim of our article was to map the current literature on management and to understand the theoretical paths that are being taken in this field. This bibliometric study selected articles published in English between 2013 and 2023, reaching a final number of 2,293 articles. The results showed that creativity is closely related to the themes of innovation, management and performance. In the analysis of thematic clusters, the evaluation of factors that contribute to and influence creativity stands out. The field appears to be plural and with a downward trend in publications.